(untitled) (UNWE Yearbook, 2022)
The paper outlines the youth profile in four SEE countries – Bulgaria, Croatia, Romania, and Slovenia by indicators that impact regional growth and resilience challenges. It contains an overview of the literature that relates growth, regional resilience and youth. The idea is to identify some directions to how youth, with their current vision for values and participation, can shape the socio-economic life of a region. The authors are using secondary data from previous research of Friedrich Ebert Foundation to interpret the youngsters’ profiles via regional development perspective and socioeconomic significance.